방송사업의 소유겸영규제 개선 - 이수일 (KDI Journal of Economic Policy, 2011)
This paper uses the horizontal regulation system as the base analysis framework. The study clearly defines the regulatory goals of the followings: the horizontal cross-ownership regulations on program provider (PP) and platform provider, the vertical regulation on cross-ownership between PP and platform operator, the regulation on cross-ownership of program provider by terrestrial broadcasting company, and the regulation on cross-ownership between terrestrial broadcasting company and platform provider. Then, by analyzing the conformity between goals and criteria of regulations and the adequacy of the regulation level according to regulatory purposes, this paper examines the justifiability of each regulation and extracts improvement measures that suite regulatory purposes. This analysis finds following appropriate measures: replacing the horizontal cross-ownership regulation on PP with conduct regulations, such as designating major broadcasting programs or replacing the current criterion of cross-ownership regulation from sales to the audience market share; reshaping the horizontal cross-ownership regulation on platform provider so that system operator (SO), satellite broadcaster and Internet protocol television (IPTV) operator would be applied by the same regulation based on the number of subscribers of pay television services; and discontinuing other cross-ownership regulation. In this way, the study shows that with appropriate regulations on cross-ownership of PP, there would be no need for additional regulation on vertical integration between PP and platform operator. On the other hand, given that the regulation on terrestrial broadcasting cross-ownership of PP could be justified only by regulatory purpose of the protection of the diversity of public opinions, it would be desirable to replace the current criteria of the number of PPs with the criteria of the audience market share. Lastly, the study shows that when platform operator is targeted by the cross-ownership regulation based on the number of subscribers of pay television services, the regulation on cross-ownership between terrestrial broadcasting company and platform provider should be replaced with conduct regulations, such as designating must-offer channels and major broadcasting programs.